Library Information System on Public Elementary School 108 Home Base Based on Android - Awaliah, Neneng; Justika, Aida; Laswi, Aishiyah Saputri; Mansyur (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
Elementary school libraries play a vital role as essential learning resources, offering diverse instructional materials that can greatly boost the reading interest of both teachers and students within the school community. These libraries also present continuous opportunities for expanding and deepening knowledge. This study focuses on creating a web-based library information system tailored for State Elementary School 108 Home Base. The system was developed using the Rapid Application Development (RAD) method, which facilitates iterative feedback and enables swift adjustments during the development process. The research findings indicate that the implemented Library Information System has been positively received by its users. The system streamlines the book borrowing process for students and staff at State Elementary School 108 Home Base and makes it easier for library administrators to manage book loans, returns, and reporting tasks. This research makes a significant contribution to the field of educational technology by offering a practical and efficient web-based solution for school library management. The use of the RAD method in system development underscores the value of incorporating user feedback to create tools that address the unique needs of educational institutions. Additionally, this study sheds light on how technology can be utilized to improve library management in elementary schools, ultimately enhancing access to educational resources and fostering a more robust reading culture among students.